2016
DOI: 10.1111/joic.12298
|View full text |Cite
|
Sign up to set email alerts
|

Women With Cardiogenic Shock Derive Greater Benefit From Early Mechanical Circulatory Support: An Update From the cVAD Registry

Abstract: Early initiation of hemodynamic support prior to PCI with Impella 2.5, in the setting of AMI complicated by CS, was associated with a greater survival benefit to hospital discharge in women compared to men, despite a higher predicted risk of mortality and a greater revascularization failure rate for women. (J Interven Cardiol 2016;29:248-256).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
45
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 28 publications
12
45
1
Order By: Relevance
“…We report in our study inhospital complications rates similar to previous reports of Impella 2.5 pLVAD use in AMICS. 15,18 In this dataset, hemolysis rate of 5.6%, bleeding requiring transfusion rate of 2.3%, vascular complications requiring surgery rate of 2.3% and device malfunction rate of 2.3% were all low. Longer dwell times for pLVAD has been associated with more hemolysis as seen in the EuroShock and cVAD registries, however, those patient cohorts demonstrated higher rates than in our patient population with a similar mean device dwell time.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…We report in our study inhospital complications rates similar to previous reports of Impella 2.5 pLVAD use in AMICS. 15,18 In this dataset, hemolysis rate of 5.6%, bleeding requiring transfusion rate of 2.3%, vascular complications requiring surgery rate of 2.3% and device malfunction rate of 2.3% were all low. Longer dwell times for pLVAD has been associated with more hemolysis as seen in the EuroShock and cVAD registries, however, those patient cohorts demonstrated higher rates than in our patient population with a similar mean device dwell time.…”
Section: Discussionmentioning
confidence: 77%
“…15 These extended DTB times in the pre-PCI group were not a determinant of adverse outcomes while on the contrary had significantly better mortality. 15,18,27 The concept of door-to-support or door-to-unloading time needs to be the new metric for patients presenting with AMI complicated with CS. This dataset has all the limitations inherent to a retrospective study.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a prior study among patients with cardiogenic shock by Joseph et al, demonstrated that female patients derived a greater benefit from Impella supported high-risk PCI. 28 Females are known to have higher risk of access site complications and the use of transradial route in percutaneous coronary intervention has been shown to reduce access site bleeding. 29 Although females had lower baseline hemoglobin and experienced more bleeding that required blood transfusion they were not at increased risk of vascular complications compared with males.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there seems to be differences in survival in-between men and women. Data from the cVAD registry (catheter-based ventricular assist device registry), a database retrospectively enrolling patients that underwent pVAD support with Impella®, showed that early initiation of hemodynamic support in patients with AMI complicated by CS was associated with a greater survival benefit in women compared to men [20]. These data are encouraging, as women usually suffer higher unadjusted mortality rates and experience the use of guideline-recommended therapies to a lesser extent.…”
Section: Cardiogenic Shockmentioning
confidence: 98%